Syllabus Design for Teaching English for Specific Purposes to Non-English Study Programs at IAIN Syaikh Abdurrahman Siddik Bangka Belitung - AZ, Indrawati; Munawwaroh, Ela Isnaini (Faculty of Social and Political Sciences University of Bangka Belitung, 2024)
This study discusses the importance of English language learning based on needs analysis with the English for Specific Purposes (ESP) approach in non-English study programs. The questionnaire results showed that 86% of students realized the importance of English for their studies and careers, while 72% liked learning English but wanted materials that were more relevant to their fields of study. As many as 58% of students considered speaking skills the most important but difficult to master, and 67% needed more practice in writing for academic needs. The majority of students (75%) liked interactive learning methods such as group discussions and simulations, and 80% agreed that learning technology was very helpful. The needs analysis showed that students of Islamic Religious Education, Early Childhood Islamic Education, Islamic Banking, and Islamic Da'wah and Communication needed materials that were relevant to their respective academic and professional contexts, such as delivering sermons, telling stories to children, presenting Islamic financial products, and participating in interfaith discussions. In addition, students expect lecturers with pedagogical, personality, professionalism, and social competencies who can create relevant and motivating learning. With a student-centered approach, English learning becomes more engaging and supports the development of applicable skills for the future.